Desenvolvimento in vitro de embriões bovinos cultivados em meio com análago de resveratrol - PATROCÍNIO, Taís T. A. (2017)
This study evaluated the effect of AR33 (patent-pending formula), a resveratrol analogue, in the culture of in vitro fertilized embryos. Cumulus-oocyte complexes (COCs) recovered from bovine ovaries collected at the slaughterhouse were matured in vitro for 24 h and fertilized in vitro for 20 h, both at 38.8 °C under 5% CO2 in air and high humidity. Probably partially nude zygotes were randomly distributed in two experiments. Experiment 1: 0 (control, n = 347), 0.1 μM (n = 337), 0.5 μM (n = 277) and 2.5 μM AR33 (n = 343) with 2.5% fetal bovine serum (FBS) and experiment 2: 2.5 μM AR33 (n = 381), 0.5 μM resveratrol (n = 381), both with 2.5% SFB and 0 (control, n = 341) with 10% FBS. The base medium for all treatments was SOFaa and incubation conditions were 38.8 °C under 5% CO2 in air and high humidity. Half of the culture medium was fed on days 3 and 5 after fertilization. The cleavage rate was evaluated on day 3 and the blastocyst rate (B1) on days 7 and 8 post-fertilization. At day 8, the blastocysts were fixed and subsequently submitted to analysis of the number of cells and apoptotic index. Cleavage and blastocyst rates were analyzed by logistic regression models (Proc Logistic), and the number of cells and apoptotic index by mixed linear models (Proc Mixed) using the SAS statistical package. In experiment 1, the cleavage rate (P <0.05) was higher at 2.5 μM (69.0 ± 4.4%) than at 0, 0.1 and 0.5 μM AR33 (62.1 ± 2.0%, 60.7 ± 5.9% and 56.7 ± 5.8%, respectively). At day 7, the Bl rate was similar (P> 0.05) between 0.1, 0.5 and 2.5 μM (18.1 ± 5.4%, 17.5 ± 2.9% and 19.4 ± 3.3%, respectively) and all were higher (P <0.05) 05) at 0 μM AR33 (12.4 ± 2.5%). At day 8, only 0.1 and 2.5 μM (21.0 ± 5.0% and 24.6 ± 3.3%) were higher than 0 μM AR33 (15.2 ± 2.5%). There was no difference (P> 0.05) between treatments regarding total cell number (TC) and internal cell mass (MCI); However, the apoptotic index in CT and MCI was higher for 0 and 2.5 μM (11.36 and 9.89%, 20.52 and 15.85%) than in 0.1 and 0.5 μM AR33 (4.66 and 4.82%, 8.47 and 10.92%). In the experiment 2 the cleavage rate (P <0.05) was higher in the control (80.8 ± 3.4%) than in the treatment with 0.5 μM resveratrol (76.4 ± 3.6%), but similar to 2.5 μM AR33 (76.9 ± 1.2%). There were no differences (P> 0.05) for the Bl rate on days 7 and 8. The apoptotic index in the CT and MCI was higher in the control (8.9 and 14.9%, respectively) than in the 2.5 μM AR33 and 0.5 μM resveratrol (6.4 and 5.5%, 11.1 and 8.8%, respectively). In conclusion, resveratrol and its synthetic analogue tested in this study improve bovine embryonic development in culture medium supplemented with 2.5% FBS under 5% CO2 in air.